Synthesis of single-crystal-like nanoporous carbon membranes and their application in overall water splitting - Wang, Hong; Min, Shixiong; Ma, Chun; Liu, Zhixiong; Zhang, Weiyi; Wang, Qiang; Li, Debao; Li, Yangyang; Turner, Stuart; Han, Yu; Zhu, Haibo; Abou-hamad, Edy; et al. (Nature communications, 2017)
Nanoporous graphitic carbon membranes with defined chemical composition and pore architecture are novel nanomaterials that are actively pursued. Compared with easy-to-make porous carbon powders that dominate the porous carbon research and applications in energy generation/conversion and environmental remediation, porous carbon membranes are synthetically more challenging though rather appealing from an application perspective due to their structural integrity, interconnectivity and purity. Here we report a simple bottom–up approach to fabricate large-size, freestanding and porous carbon membranes that feature an unusual single-crystal-like graphitic order and hierarchical pore architecture plus favourable nitrogen doping. When loaded with cobalt nanoparticles, such carbon membranes serve as high-performance carbon-based non-noble metal electrocatalyst for overall water splitting. Hierarchical, nanoporous graphitic membranes are synthetically challenging yet attractive materials, due to their structural integrity. Here, the authors fabricate freestanding, porous carbon membranes with single-crystal-like graphitic order which serve as water splitting electrocatalysts upon cobalt doping.